2021
DOI: 10.3389/fmicb.2021.722225
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Streptococcus pyogenes Isolated From Chinese Children With Different Diseases

Abstract: Streptococcus pyogenes is a bacterial pathogen that causes a wide spectrum of clinical diseases exclusively in humans. The distribution of emm type, antibiotic resistance and virulence gene expression for S. pyogenes varies temporally and geographically, resulting in distinct disease spectra. In this study, we analyzed antibiotic resistance and resistance gene expression patterns among S. pyogenes isolates from pediatric patients in China and investigated the relationship between virulence gene expression, emm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
(66 reference statements)
1
8
0
1
Order By: Relevance
“…In this study, we presented distribution of emm types including 13 emm types and 11 sAgs. Types emm12.0 and emm1.0 exhibited higher polymorphism rate which were similar with our previous study as well as Yu' study from 2016 to 2018 [9]. They were responsible for about 73.81% of scarlet fever cases in our present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we presented distribution of emm types including 13 emm types and 11 sAgs. Types emm12.0 and emm1.0 exhibited higher polymorphism rate which were similar with our previous study as well as Yu' study from 2016 to 2018 [9]. They were responsible for about 73.81% of scarlet fever cases in our present study.…”
Section: Discussionsupporting
confidence: 92%
“…Resistance rate of macrolides in our present study was still high compared with our previous studies from 2016 to 2017, and 2019. Yu found that from 2016 to 2018, 342 GAS strains were highly susceptible to penicillin, levofloxacin, and chloramphenicol, whereas most of strains were resistant to azithromycin, erythromycin, clarithromycin, clindamycin, and tetracycline [ 9 ]. Since 1990, the resistance rate of GAS against clindamycin and macrolides has been high [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A key exception to Fleming 's warning about the relationship between antimicrobial use and the development of resistance is the persistent susceptibility of GAS to b-lactam antibiotics (Horn et al, 1998). Eighty years after the introduction of penicillin, GAS strains still maintain consistent susceptibility to various b-lactams, and even the MICs of GAS to blactams remain low and stable (Yu et al, 2021a). The reasons for the persistent susceptibility of GAS to b-lactams are unclear, but may include differences in the rate and mechanism of horizontal gene transfer between GAS and other Streptococci.…”
Section: Interpretation Criteria For Antimicrobial Susceptibility Tes...mentioning
confidence: 99%